HASIL BELAJAR SISWA SETELAH PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING PADA MATERI ZAT ADITIF - Putri Wahyu Imania (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2019)
This study aimed to describe student learning outcomes after the application of the Snowball Throwing learning model on the Additive Substance material. This type of research was a quantitative descriptive research. The form of design used was the one-shot case study. This research was conducted in 1 meeting with a time allocation of 3 × 40 minutes or 120 minutes. The instrument used was in the form of test questions for students' cognitive understanding. Data collection was obtained from student learning outcomes (posttest) expressed as student completeness and learning indicator completeness. Student learning outcomes data (posttest) showed that learning using the Snowball Throwing model has created a success in learning that was the average grade value was 75.77 while the Minimum Criteria Completeness on science subjects was 65. Mastery Learning Indicators (KIP) in this study amounted to 76.45. This study showed that learning using the Snowball Throwing model has completed student learning outcomes and learning indicators.